Employability of graduates of Stomatology - Carrasco, Milagros (2021)
Objective: To evaluate the employability of the stomatology graduates based on the National Survey of University Graduates 2014 of the National Institute of Statistics and Informatics. Material and methods: The research was descriptive, retrospective and transversal. The study population included 245 graduates from 33 universities in the country, from 2006 to 2010. Results: 79.6% of the graduates were employed and mainly as dentists (77.3%), with an average of 33.8 hours per week worked hours and an economic compensation of 505.3 soles. 33,5% of the graduates were in Lima, 68.25% graduates, 21.2% with a bachelor’s degree and 33.5% with postgraduate studies. 22.2% had another job, mainly dentistry (66.5%). 35.1% changed employment and the first job was related to the profession in 96.5%. The time it takes to get the first job is less than one month (40.7%) and through family and friends (37,2%). Conclusions: Stomatology graduates acquired skills for employability.